« Cette heureuse contrée deviendra désormais une terre de promission » : la Révolution française écrite par des témoins britanniques à Paris - Rachel Rogers (Astérion)
A number of British men and women who were active in the movement for parliamentary reform in Great Britain settled in Paris after the fall of the Bastille in July 1789 to witness and take part in the events of the French Revolution at first hand. For some, it was the fall of the monarchy on the 10th of August 1792 that became the catalyst of their political activism on French soil. This article seeks to situate the writings of members of the British community in Paris on the French Revolution within their broader diplomatic and political context. First it examines the way the French Revolution was seen from a British perspective before going on to explore the creation of the political club that brought together British and Irish residents of Paris who were supportive of the French Revolution, which became known by the name “Society of the Friends of Human Rights”. It will then consider the different perspectives offered by British residents on the drafting of the new republican constitution written between October 1792 and February 1793, paying particular consideration to the way in which British observers approached the question of a government based on popular sovereignty. Finally, it sheds light on the way in which these authors – eyewitnesses of the events they reported on – understood the Revolution and how they attempted, through emphasis on the veracity of their accounts, to shape national opinion in their home country.